BDNF/TrkB/Akt Signaling Pathway Epithelial Odontogenic Tumors and Keratocyst: An Immunohistochemical Study Comparative With Dental Germs. Issue 5 (15th May 2021) - Dornelles, Florencia M.L.; Wagner, Vivian P.; Fonseca, Felipe P.; Ariotti, Carla; Carrard, Vinicius C.; Vargas, Pablo A.; Sánchez-Romero, Celeste; Beovide, Veronica; Bologna-Molina, Ronell; Martins, Manoela D.
Abstract : Supplemental Digital Content is available in the text. Abstract : Odontogenic lesions (OL) are an important group of oral and maxillofacial diseases represented by odontogenic cysts, benign, and malignant tumors. The brain-derived neurotrophic factor (BDNF)/ tropomyosin receptor kinase B (TrkB) signaling pathway has multiple biological actions and has been identified as an important pathway in the proliferation, invasion, and survival of different epithelial tumors. Its role in the development of OL, however, has so far been unexplored. Our aim was to evaluate the BDNF/TrkB/Akt/p-RPS6 signaling pathway in OL of epithelial origin. This cross-sectional study comprised 3 cases of tooth germs, 25 cases of odontogenic keratocyst (OK), 29 cases of ameloblastoma (Am), and 6 cases of ameloblastic carcinoma. Immunohistochemical staining for BDNF, TrkB, p-Akt, and p-RPS6 was performed. OLs were evaluated according to the pattern of immunohistochemical expression in epithelial cells and by semiquantitative scores that considered the intensity of staining and percentage of positive cells. BDNF stromal expression was also assessed. No significant differences were observed with respect to the percentage of positive cases for all markers. Regarding the immunoreactive scores, BDNF and p-RPS6 expressions were similar in the odontogenic epithelium of all OL. However, TrkB and p-Akt were overexpressed in OK compared with ameloblastic carcinoma. In Am, epithelial BDNF was significantly higher compared with stromal expression. In conclusion, BDNF seems to participate in the development of cystic, benign, and malignant odontogenic epithelium to similar degrees. The acquisition of the invasive or malignant phenotype in odontogenic neoplasms is not associated with alterations in the BDNF/TrkB/Akt/RPS6 axis, which could be implicated in the differentiation process.